Culture of use leisure time - Pljakić Goran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
A man, as a social being, has to change constantly through the adoption and creation of new achievements of modern civilization. To even make it possible, one must organize one's time so that it is put in function of one's permanent development. The author has found, by analysing relevant literature, that the role of the individual in the leisure time in today's society is largely reduced to the consumer role. It was found that the eminent experts agree with the fact that the need for personal development and self-realisation through creative expression, which includes active participation in family social, sports and other activities, is given less opportunity for expression and development. The mass consumer culture vocally promotes consumption of trash and kitsch, which is reflected in the dominance of objects in the system of value, while the genuine cultural values are depreciated. Leisure time, as one of the key factors to the development of young people, must be in function of making a person capable to critically evaluate cultural values, but also their own cultural consumption, participation and creativity in the cultural sphere.